THE EFFECT OF ENVIRONMENTAL, SOCIAL AND GOVERNANCE DISCLOSURE ON FIRM VALUE IN ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN THE 2021-2023 PERIOD - Sinaga, Priskila; Simanjuntak, Arthur; Sagala, Farida; Ginting, Mitha Christina (Jurnal Ilmiah Accusi, 2025)
This study aims to examine the effect of Environmental, Social, and Governance Disclosure (ESG) on firm value. The dependent variable used in this study is firm value measured using Tobin's Q, PBV, and PER. While the independent variable ESG Disclosure is measured based on the ESG disclosure index adjusted to the Global Reporting Initiative (GRI) guidelines and measured using CSRIj. This study uses a quantitative approach with secondary data obtained from the company's annual report and sustainability report during the observation period and the data used in this study were obtained from the company's website or the IDX website (BEI). The population used in the study were energy sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample of this study was determined using the purposive sampling method, so that the number of samples that met the criteria was 67 company data. The research hypothesis testing used multiple linear regression analysis. This study processes data using Microsoft Excel and conducts testing using SPSS 25 software. The results of this study indicate that Environmental, Social, and Governance Disclosure have an effect on company value (Firm Value)